GROWTH OF DIGITAL PAYMENT APPS IN INDIA-A STUDY - Yogesh kumar,; Dr.Amalanathan.P, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The world has been shifting toward all things digital for a very long time. But the year 2020 made clear how critical it is to quickly adopt new technology. This modification took place fairly immediately after the lockdown was put into place, especially in India for digital payments. Since demonetization in 2016 the Indian government has aggressively promoted and spread online payments. The myriad economic and financial considerations that compelled Indians to change online payments were all motivated by the idea of "Digital India." Making sure there is financial equality becomes a matter of the utmost significance in a country like India where differences might occasionally be different.